An evaluation of bottleneck bandwidth and round trip time and its variants - Zhang, Songyang; Lei, Weimin; Zhang, Wei; Li, Hao (International journal of communication systems, 2021)
Summary The congestion control mechanism is one of the most important components in Internet, which guarantees network normal operation and prevents network from congestion collapse. It is noticed that traditional loss‐based algorithms are not moving data very well in today's Internet. To get channel resource highly utilized, such algorithms maintain a standing queue of packets at bottleneck and cause large transmission delay. Recently, effort has been devoted from academia and industry to design new solution which could achieve high throughput and low transmission delay simultaneously. There are several fruitful results such as the bottleneck bandwidth and round trip time (BBR) and Vivace, Copa, Cellular Controlled delay TCP (C2TCP). Among them, BBR is the most eminent one. There are other variant algorithms by modifying some parameters in BBR for possible improvement, and BBR has also evolved drastically into version 2 (BBRv2). In this work, a framework is implemented to evaluate the performance of these algorithms on ns3. Interested readers could test other congestion control algorithms or design new methods. Moreover, this work can work as reference for engineers to tune parameters in BBR or choose other solutions for their applications. We present a framework to evaluate the performance of several recently proposed congestion control algorithms (BBR, BBR', BBRPlus, BBR+, Tsunami BBR v2, Vivace, Copa, and C2TCP) on ns3 platform. Parameters involved in evaluation are inter‐protocol fairness, packet loss rate, one‐way transmission delay, and channel utilization. Interested reader could develop and test new congestion schemes in an easier way.